Desain Ulang Sandal Gunung Dan Sandal Jepit Everest Menggunakan Quality Function Deployment (Qfd) - Mulyono, Frisma Sri; , Siti Nandiroh, ST., M.Eng; , Hafidh Munawir, ST., M.Eng (2016)
Abstracts The purchasing power of the community demanding company to producing goods to suit the needs of desired consumers with lower prices for relatively low but still give the quality good. The quality of goods is a form of assessment on the level of consumer goods bought to the level of goods expected (expected services). Sandals the mountains and sandals flops owns the "EVEREST" is the product that is still thriving and consequently there is a shortage of felt by consumers. Hence, research to the design of sandals the mountains and sandals flops this is necessary so product quality produced increased. This report aims to review the consumer advocacy to be used for redesign product slippers mountains and slippers flops "EVEREST" using the from analysis qfd (quality function deployment). This research result indicates that variabel-variabel affecting consumers to buy slippers mount everest and slippers flops is a sandals, color and motives sandal more variatif, design comfortable and durable, the quality of material used, the increased availability of size varying, and prices economical. But the problems often experienced by the user slippers the and slippers flops "EVEREST" include webbing connector susceptible drop out, the use of glue low quality so easily have a rope, raw rubber soft so quickly up and variation of color and motives less.